Heptamethine cyanine-based polymeric nanoparticles for photothermal therapy in HCT116 human colon cancer model - Sastiya Kampaengsri; Gong Yi Yong; Sirimongkon Aryamueang; Bongkot Ouengwanarat; Thitima Pewklang; Kantapat Chansaenpak; Sarawut Jitrapakdee; Chin-Siang Kue; Anyanee Kamkaew (Scientific Reports)
Abstract In this work, we synthesize a quinoline-based heptamethine cyanine, QuCy7, with sulfonate groups to enhance water solubility. This dye demonstrates exceptional near-infrared absorption beyond 750 nm, accompanied by photothermal properties but low photostability. Encapsulating QyCy7 with polyethylene glycol to form nanopolymer, QuCy7@mPEG NPs, addresses the issue of its photoinstability. TEM showed that QuCy7@mPEG NPs possess a spherical morphology, featuring a core-shell structure with a size of around 120 nm in diameter. Upon irradiation with an 808 nm laser for 10 min, a significant increase in temperature up to 24 °C can be achieved with a photothermal conversion (PTC) rate of approximately 35%. QuCy7@mPEG NPs exhibit remarkable photothermal stability as compared to QuCy7. The efficiency of QuCy7@mPEG NPs was demonstrated by the in vitro PTT studies. Finally, the nanoparticles’ acute toxicity and effectiveness were assessed using the chick embryo model. The results provide compelling evidence that QuCy7@mPEG NPs are safe without inducing hemolysis, inhibit angiogenesis when exposed to light, and exhibit anti-tumor activity with a 76% reduction in tumor size compared to QuCy7 (40%). Thus suggesting the sulfonate groups can enhance water solubility, and its nanopolymer is biocompatible and possesses superior anti-tumor efficacy.